Assessing Millets and Sorghum Consumption Behavior in Urban India: A Large-Scale Survey - Kane-Potaka, Joanna; Anitha, Seetha; Tsusaka, Takuji W.; Botha, Rosemary; Budumuru, Muralidhar; Upadhyay, Shweta; Kumar, Parkavi; Mallesh, Karuna; Hunasgi, Raghavendra; Jalagam, Ashok Kumar; Nedumaran, Swamikannu (Frontiers in Sustainable Food Systems, 2021)
There is growing attention by governments and industry in regard to the role played by millets (including sorghum) to help build resilience for farmers and cope with climate change, malnutrition, diabetes, and some other major issues. To understand public knowledge and practices of consuming millets in urban areas, a survey was conducted with 15,522 individuals from seven major cities of India using a structured questionnaire, and after data cleaning 15,139 observations were subjected to analysis using descriptive and inferential statistics. It was found that the largest group among early adopters of millets were people with health problems (28%), it being the single largest reason for consuming millets, followed by those wanting to lose weight (15%) and those selecting millets for its taste (14%). There was a significant gap between people who were health conscious (91%) and those who were sure millets were healthy (40%). The major reason the respondents did not eat more millets was that it was not eaten at home (40%), followed by reactions such as not liking the taste (22%). Reaching the urban consumers through social media is recommended, given that it is their main source of information. There was no statistically significant relationship between state-wise per capita production and frequency of consumption of millets in the urban areas (p = 0.236). In conclusion, three key actions are recommended to enhance the consumption of millets: developing delicious products to satisfy the taste, providing knowledge on nutritional and health facts on millets, and improving accessibility of millets in urban markets.